Anti-Cancer Effects of Lycopene in Animal Models of Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis - Mekuria, Abraham Nigussie; Tura, Abera Kenay; Hagos, Bisrat; Sisay, Mekonnen; Abdela, Jemal; Mishore, Kirubel Minsamo; Motbaynor, Birhanu (Frontiers in Pharmacology, 2020)
Introduction: Globally, hepatocellular carcinoma (HCC) is the sixth most diagnosed cancer and the third important cause of cancer-related death. As there are only two targeted drugs for the treatment of advanced HCC—that merely extend survival by a few months—the need for alternative treatments is inevitable. Lycopene, a carotenoid that is known to be most abundant in red tomatoes and tomato-based products, has been investigated for its anticancer activity in various types of cancers including HCC. This review was conducted to evaluate the effects of lycopene on HCC from animal models to pave the way for further clinical studies. Methods: Electronic databases and search engines including PubMed, EMBASE, and Google Scholar were searched for original records addressing the anticancer effect of lycopene in animal models of HCC. Data were extracted using a format prepared in Microsoft Excel and exported to Stata 15.0 for analyses. A meta-analysis was performed using a random-effects model at a 95% confidence level for the outcome measures: tumor incidence, number, and growth (tumor volume and size). The presence of publication bias between studies was evaluated using Egger’s test and funnel plot. The study protocol was registered in the PROSPERO database with reference number: CRD42019159312. Results: The initial database search yields 286 articles, of which 15 studies met the inclusion criteria. The characteristics of the included studies were a bit diversified. The studies involved a total of 644 animals (312 treatment and 332 control groups) and mice shared the majority (488) followed by rats (117) and ferrets (39). The meta-analysis showed that lycopene significantly reduced the incidence [RR 0.8; 95% CI 0.69, 0.92 (p=0.00); I2=30.4%, p=0.16; n=11], number [SMD-1.83; 95% CI -3.10, -0.57 (p=0.01); I2=95.9%, p=0.00; n=9], and growth [SMD -2.13; 95% CI -4.20, -0.04 (p=0.04); I2=94.6%, p=0.00; n=4] of HCC. Conclusions: Administration of lycopene appears to inhibit the initiation and progression of cancer in animal models of HCC. However, more controlled and thorough preclinical studies are needed to further evaluate its anti-HCC effects and associated molecular mechanisms.